On primordial sense-antisense coding - Rodin, Andrei S. (2009)
The genetic code is implemented by aminoacyl-tRNA synthetases (aaRS). These twenty enzymes are divided into two classes that, despite performing same functions, have nothing common in structure. The mystery of this striking partition of aaRSs might have been concealed in their sterically complementary modes of tRNA recognition that, as we have found recently, protect the tRNAs with complementary anticodons from confusion in translation. This finding implies that, in the beginning, life increased its coding repertoire by the pairs of complementary codons (rather than one-by-one) and used both complementary strands of genes as templates for translation. The class I and class II aaRSs may represent one of the most important examples of such primordial sence-antisence (SAS) coding (Rodin and Ohno, 1995). In this report, we address the issue of SAS coding in a wider scope. We suggest a variety of advantages that such coding would have had in exploring a wider sequence space before translation became highly specific. In particular, we confirm that in Achylia klebsiana a single gene might have originally coded for an HSP70 chaperonin (class II aaRS homolog) and an NAD-specific GDH-like enzyme (class I aaRS homolog) via its sense and antisense strands. Thus, in contrast to the conclusions in (Williams et al., 2009), this could indeed be a “Rosetta stone” (eroded somewhat, though) gene for the SAS origin of the two aaRS classes (Carter and Duax, 2002).